PENGARUH MEDIA PUZZLE DIGITAL TERHADAP KEMAMPUAN VISUAL SPASIAL ANAK USIA 5-6 TAHUN DI TK PERMATA INSANI ISLAMIC SCHOOL KOTA JAMBI - Salsabilla, Ririn; Muazzomi, Nyimas; Sherly Utami, Winda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by observations indicating problems in children’s visual-spatial abilities. Out of 10 children in group B3, 8 were found to have low visual-spatial skills, which may hinder their future development. The purpose of this study was to determine the effect of digital puzzle media on the visual-spatial abilities of children aged 5–6 years at TK Permata Insani Islamic School, Jambi City. The research used a pre-experimental method with a one group pretest-posttest design. The sample consisted of 10 children selected through simple random sampling from a population of 33 children. Data were collected through observation and documentation using validated instruments, and analyzed using normality, homogeneity, and paired samples t-test. The results showed a significance value of 0.000 < 0.05, indicating that digital puzzle media had a positive effect on children’s visual-spatial abilities. The effect size was 6.33, categorized as a very strong effect. Therefore, digital puzzle media is effective in improving the visual-spatial abilities of children aged 5–6 years.